Принцип увеличения частоты генерируемого сигнала в мультивибраторе Ройера - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
The principle of increasing the frequency of signal generation of a Roier multivibrator on the basis of the discharge of a capacitor to zero during the cut-off of a transistor is proposed.